Systematic identification and characterization of regulatory elements derived from human endogenous retroviruses - Ito, Jumpei (PLoS Genet, 2017)
Human endogenous retroviruses (HERVs) and other long terminal repeat (LTR)-type retrotransposons (HERV/LTRs) have regulatory elements that possibly influence the transcription of host genes. We systematically identified and characterized these regulatory elements based on publicly available datasets of ChIP-Seq of 97 transcription factors (TFs) provided by ENCODE and Roadmap Epigenomics projects. We determined transcription factor-binding sites (TFBSs) using the ChIP-Seq datasets and identified TFBSs observed on HERV/LTR sequences (HERV-TFBSs). Overall, 794,972 HERV-TFBSs were identified. Subsequently, we identified “HERV/LTR-shared regulatory element (HSRE),” defined as a TF-binding motif in HERV-TFBSs, shared within a substantial fraction of a HERV/LTR type. HSREs could be an indication that the regulatory elements of HERV/LTRs are present before their insertions. We identified 2,201 HSREs, comprising specific associations of 354 HERV/LTRs and 84 TFs. Clustering analysis showed that HERV/LTRs can be grouped according to the TF binding patterns; HERV/LTR groups bounded to pluripotent TFs (e.g., SOX2, POU5F1, and NANOG), embryonic endoderm/mesendoderm TFs (e.g., GATA4/6, SOX17, and FOXA1/2), hematopoietic TFs (e.g., SPI1 (PU1), GATA1/2, and TAL1), and CTCF were identified. Regulatory elements of HERV/LTRs tended to locate nearby and/or interact three-dimensionally with the genes involved in immune responses, indicating that the regulatory elements play an important role in controlling the immune regulatory network. Further, we demonstrated subgroup-specific TF binding within LTR7, LTR5B, and LTR5_Hs, indicating that gains or losses of the regulatory elements occurred during genomic invasions of the HERV/LTRs. Finally, we constructed dbHERV-REs, an interactive database of HERV/LTR regulatory elements (http://herv-tfbs.com/). This study provides fundamental information in understanding the impact of HERV/LTRs on host transcription, and offers insights into the transcriptional modulation systems of HERV/LTRs and ancestral HERVs.